Budget Politics in the Implementation of Social Assistance Programs (Case Study of Stunting Programs in Depok City) - Rizky Putri Anggraini; Fatkhuri Fatkhuri (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This study aims to analyze the case study of the Stunting Program. The case study aims to find out how the role of the Depok City Provincial Government in preparing budget allocations in budgeting for social assistance for stunting programs in Depok City and how the implementation of the stunting social assistance program in Depok City itself sees that there are still several problems in the implementation process. By reviewing the case study, it is hoped that later it can provide solutions and improvements in the implementation of social assistance in the stunting program in Depok City. The prevalence of stunting in Depok City fluctuates from year to year. In achieving a reduction in stunting rates in toddlers, especially through regional financial policies and the APBD, the Depok City government must consider the regional financial situation and set development priorities. The research method used in this study is qualitative with a case study strategy that is analyzed descriptively and the number of respondents is 2 informants. The result of this study is that there is still a lack of data optimization in the synchronization of beneficiary data and a lack of public awareness of the importance of stunting reduction programs. Therefore, the recommendation of this study is the need for the role and cooperation of all parties involved, both internal and external, as well as increasing socialization media to provide confirmation about the importance of preventing stunting.